Improvement Science as a Promising Alternative to Barriers in Improving STEM Teacher Quality through Professional Development. Issue 1 (4th March 2019) - Wright, Kim B.
Abstract: STEM teaching occurs within national and state policy contexts that are constantly shifting in terms of standards and accountability due to the current and intense focus on students' STEM outcomes. In the last two decades, federal legislation as well as common standards movements increasingly influence what and how STEM teachers instruct their students. Improvement science in education (ISE) has recently emerged as a new method of addressing many of the issues that impact teacher teaching and STEM teacher quality. ISE is a context-focused process improvement approach targeted at school improvement. This article explores three main barriers between STEM teacher professional development and student learning, and focuses on ISE as a promising alternative to current forms of STEM teacher professional development.